Pemanfaatan Limbah Tanaman Sebagai Sumber Pupuk Organik Cair (POC) Untuk Penurunan Ongkos Produksi Kelapa Sawit Di Kecamatan Pagar Merbau - Aulia Wardani; Nina Novira; Friska Adelia Sari; Raihan Fadhilah; Miko Valentino Sipayung; Adam Dwi Cahya Barus (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This research aims to utilize plant waste as raw material for making liquid organic fertilizer (POC) to reduce the cost of palm oil production in Pagar Merbau District. The methods used include collecting vegetable and fruit waste, fermentation process with EM4 bioactivator, and POC packaging. The research results show that the use of plant waste can reduce the cost of palm oil production due to the high use of chemical fertilizers so that farmers find it difficult to fertilize due to high prices. Utilizing plant waste as a source of liquid organic fertilizer (POC) can provide benefits to oil palm farmers and can also support more sustainable and environmentally friendly agricultural practices.